Multivariate analysis of plant transpiration and copper uptake of Phragmites karka in a lysimeter scale set-up an approximation under subsurface flow constructed wetland - Liwag, Nicasio Chuck G.; Dalida, Maria Lourdes C.; Resurreccion, Augustus C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
A study was conducted for a comprehensive characterization of the transpiration process of Phragmites karka and its copper uptake behaviour under Philippine climate condition, an impetus for the initial establishment of cultural management practice for the said reed plant in a constructed wetland box. A Soil-Plant Atmosphere Research chamber was customized to measure actual transpiration under varied combinations of natural standing biomass parameters (plant height and leaf biomass) together with manipulated combination s of atmospheric conditions (Wind speed, atmospheric temperature, relative humidity and solar illuminance). A total of forty three (43) Phragmites karka transplanted in pebbles media housed in weighable lysimeters with recirculating pump, operating as a hydrophonic system, were used. The study brought forth an empirical transpiration model function involving standing biomass (plant height and leaf biomass) interacting together with the surrounding atmospheric conditions (wind speed, atmospheric temperature, relative humidity, and solar illuminance). The derived transpiration model showed an optimal (relative minimum) transpiration rate at condition pertaining to plant height and leaf biomass of a domesticated young tillering Phragmites karka. A field test was done to assess the predictive ability of the empirical transpiration model. The predictive performance acceptably faired with a value of Pearson correlation coefficient of 0.9414 and a 28.28% Residual Mean Square Error value. Copper metal uptake experiment was also conducted to assess the effect of standing biomass parameters and pH of solution. A mine tailing approximated Cu2+ concentration of 26 ppm was prepared in two pH solutions (pH 4 and pH 6). Six varying plant heights (2 domesticated young tillers between 1 meter to 2 meters, 2 towering tillers between 2 meters and 3 meters and 2 flowering tillers of Phragmites karka) were tested under pH 4 and pH 6 solution. It was shown that domesticated young tillering Phragmites karka accumulated and sequestered more copper than the adult and higher reed plants. The young reed plant accumulated and sequestered more copper under pH 4 solution. The result of the experiment led to a recommendation for the development of a pruning scheme that would encourage domestication of young tillering Phragmites karka from established bunches of adult reed plant population .
Thesis (Ph.D. Environmental Engineering)--University of the Philippines Diliman
Keywords: Phragmites; Plants -- Transpiration